2015
DOI: 10.1111/mec.13184
|View full text |Cite
|
Sign up to set email alerts
|

A genetic perspective on rapid evolution in cane toads (Rhinella marina)

Abstract: The process of biological invasion exposes a species to novel pressures, in terms of both the environments it encounters and the evolutionary consequences of range expansion. Several invaders have been shown to exhibit rapid evolutionary changes in response to those pressures, thus providing robust opportunities to clarify the processes at work during rapid phenotypic transitions. The accelerating pace of invasion of cane toads (Rhinella marina) in tropical Australia during its 80-year history has been well ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 91 publications
5
129
0
Order By: Relevance
“…Surprisingly, we still know little about what traits comprise successful invaders, especially for vertebrates. Perhaps the best-studied introduced vertebrate species is the cane toad (Rhinella marina), which spread across Australia in ∼80 years (Phillips et al, 2006;Kolbe et al, 2009;Brown and Shine, 2014;Brown et al, 2015a,b;Rollins et al, 2015). Other non-native vertebrates, particularly rodents and songbirds (Losos et al, 1997;Kolbe et al, 2004;Lee et al, , 2005Fassbinder-Orth et al, 2013;Vilcinskas et al, 2013;White et al, 2013;Morand et al, 2015;Tian et al, 2015), have gained some recent attention, but the diversity of research approaches makes generalizations about facilitators of range expansions premature.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we still know little about what traits comprise successful invaders, especially for vertebrates. Perhaps the best-studied introduced vertebrate species is the cane toad (Rhinella marina), which spread across Australia in ∼80 years (Phillips et al, 2006;Kolbe et al, 2009;Brown and Shine, 2014;Brown et al, 2015a,b;Rollins et al, 2015). Other non-native vertebrates, particularly rodents and songbirds (Losos et al, 1997;Kolbe et al, 2004;Lee et al, , 2005Fassbinder-Orth et al, 2013;Vilcinskas et al, 2013;White et al, 2013;Morand et al, 2015;Tian et al, 2015), have gained some recent attention, but the diversity of research approaches makes generalizations about facilitators of range expansions premature.…”
Section: Introductionmentioning
confidence: 99%
“…Resting MR has been previously found to be higher in individuals with greater movement propensity (Niitepõld et al 2009;Myles-Gonzalez et al 2015) and a recent study found that genes underlying metabolic processes are upregulated in dispersive cane toads (Rollins et al 2015). Given the potential involvement of genetic and epigenetic mechanisms, and potential metabolome differences between dispersive and non-dispersive individuals (Rollins et al 2015;Van Petegem et al 2015;2016b), it may be worth exploring the association between MR and movement in other systems. Burton et al 2011;Killen et al 2012;Killen et al 2013;Lebeau et al 2016;Metcalfe et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…If differences in these traits are apparent between resident and disperser larvae (which seems highly probable), then it would be insightful to examine the expression of genes involved in metabolic processes and their regulation. Recent studies have found that the genetics, epigenetics, and metabolomics can differ between resident and disperser toads (Rollins et al 2015) and spider mites (Van Petegem et al 2016b). …”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations